Stress Management Strategies Adopted by Postgraduate Working Mothers: Case Study of University of Port Harcourt, Rivers State - C.U, Sonye; N. O, Abiamuwe; M , Bamson; F.O, Maduabum (Journal of Home Economics Research, 2024)
The paper focused on stress management strategies adopted by postgraduate working mothers in University of Port Harcourt, Rivers State. Six research questions guided the study. It was a survey. The population for the study was 2,503 postgraduate working mothers. The sample size was 300 postgraduate working mothers drawn by convenience sampling technique. Questionnaire and Focus Group Discussion (FGD) guide were used for data collection. Data were analysed using mean. Findings of the study revealed 48 causes of stress at home, school and work place; 32 coping strategies that will help postgraduate working mothers to cope with stress at home, school and work places; as being organized, focusing at school work while at school, office work while at work and house chores and family matters while at home, among others . Among recommendations made was that postgraduate working mothers should adopt flexible working hours and maintain a balance between work and work life by scheduling work properly.